Explicitly self-similar solutions for the Euler/Navier–Stokes–Korteweg equations in RN. (May 2017) - Chen, Yang; Fan, Engui; Yuen, Manwai
Abstract: In this paper, we present a unified formulae for explicit self-similar solutions of the Euler/Navier–Stokes–Korteweg equations arising in the modeling of capillary fluids. The technique used here is to reduce Euler/Navier–Stokes–Korteweg equations into a series of solvable ordinary differential equations by making use of multi-dimensional self-similar ansatz and variable separation method.